Clinical and psychological aspects of hypoglycemia in patients with diabetes mellitus - Olga Georgievna Mel'nikova (Endocrinology Research Centre, 2010)
This paper reviews key aspects of hypoglycemia in patients with diabetes mellitus. The description and classification of hyoglycemias are presented inconformity with criteria of American Diabetes Association, European Agency for Evaluation of Medicinal Products, Canadian Diabetes Association,and Russian Algorithm of specialized care for diabetic patients. The main factors responsible for the development of hypoglycemia and its clinicalpicture are considered. A detailed characteristic of abnormal sensitivity to hypoglycemia is given. Psychological aspects of the effects of hypoglycemiaon the quality of life and achievement of target parameters of glycemic control are analysed.